2014
DOI: 10.1210/en.2014-1308
|View full text |Cite
|
Sign up to set email alerts
|

Low Calcium-Phosphate Intakes Modulate the Low-Protein Diet-Related Effect on Peak Bone Mass Acquisition: A Hormonal and Bone Strength Determinants Study in Female Growing Rats

Abstract: Peak bone mass acquisition is influenced by environmental factors including dietary intake. A low-protein diet delays body and skeletal growth in association with a reduction in serum IGF-1 whereas serum FGF21 is increased by selective amino acid deprivation. Calcium (Ca) and phosphorous (P) are also key nutrients for skeletal health, and inadequate intakes reduce bone mass accrual in association with calciotropic hormone modulation. Besides, the effect of calcium supplementation on bone mass in prepubertal ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Dietary Ca 2+ stimulates FGF23 production , and a Ca 2+ deficit lowers FGF23 . Ca 2+ ‐dependent regulation of FGF23 seems to be independent of PTH/vitamin D and possibly be due to a direct effect on Fgf23 gene expression via calcium channels .…”
Section: Homeostatic Regulation Of Fgf23mentioning
confidence: 96%
“…Dietary Ca 2+ stimulates FGF23 production , and a Ca 2+ deficit lowers FGF23 . Ca 2+ ‐dependent regulation of FGF23 seems to be independent of PTH/vitamin D and possibly be due to a direct effect on Fgf23 gene expression via calcium channels .…”
Section: Homeostatic Regulation Of Fgf23mentioning
confidence: 96%
“…In fact, restricting energy intake without restricting protein decreased FGF21 expression. Subsequent work by multiple groups has confirmed that FGF21 is robustly increased by dietary protein restriction (Fournier et al, 2014; Ozaki et al, 2015; Chalvon-Demersay et al, 2016; Gosby et al, 2016; Maida et al, 2016; Pezeshki et al, 2016; Solon-Biet et al, 2016; Larson et al, 2017; Pereira et al, 2017a). This effect to increase FGF21 also extends to other situations of amino acid restriction, including the restriction of leucine, methionine/cysteine, the depletion asparagine, and the restriction of multiple non-essential amino acids (De Sousa-Coelho et al, 2012; Wanders et al, 2015; Wilson et al, 2015; Maida et al, 2016; Wanders et al, 2017).…”
Section: Nutritional Regulation Of Liver Fgf21 Expressionmentioning
confidence: 98%
“…Chronic protein deficiency has been reported to delay skeletal growth and bone maturity and cause fatty infiltration of the liver in infants and young children, conditions that are often associated with chronic malnutrition, a major factor affecting child morbidity and mortality in developing countries [10,11]. It has been reported that a low-protein diet reduces tibia length and diameter, and bone mineral content (BMC) in growing rats [12] and children [13]. Also low levels of circulating IGF-1 and the presence of a fatty liver are conditions frequently observed in children with a protein-deficient diet [14].…”
Section: Introductionmentioning
confidence: 99%